aboutsummaryrefslogtreecommitdiff
path: root/gupta/hw6.tex
blob: 4362d262ef40a6488752f4b8c225a5582aa96791 (plain)
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
\newfam\bbold
\def\bb#1{{\fam\bbold #1}}
\font\bbten=msbm10
\font\bbsev=msbm7
\font\bbfiv=msbm5
\textfont\bbold=\bbten
\scriptfont\bbold=\bbsev
\scriptscriptfont\bbold=\bbfiv
\font\bigbf=cmbx12 at 24pt

\def\answer{\smallskip{\bf Answer.}\par}
\def\endproof{\leavevmode\hskip\parfillskip\vrule height 6pt width 6pt
depth 0pt{\parfillskip0pt\medskip}}
\let\endanswer\endproof
\def\section#1{\medskip\vskip0pt plus 1in\goodbreak\vskip 0pt plus -1in%
\noindent{\bf #1}}
\let\impl\to
\def\nmid{\hskip-3pt\not\hskip2.5pt\mid}
\def\problem#1{\par\penalty-100\item{#1}}

\headline{\vtop{\hbox to \hsize{\strut Math 2106 - Dr. Gupta\hfil Due Thursday
2022-02-17 at 11:59 pm}\hrule height .5pt}}

\centerline{\bigbf Homework 6 - Holden Rohrer}
\bigskip

\noindent{\bf Collaborators:} None

\section{Hammack 10: 4, 8, 20, 26}
Prove the following statements with either induction, strong induction,
or proof by smallest counterexample.

\problem{4.} If $n\in\bb N,$ then $1\cdot 2 + 2\cdot 3 + 3\cdot 4 +
4\cdot 5 + \cdots + n(n+1) = {n(n+1)(n+2)\over 3}.$

\answer
We will show that $\sum_{k=1}^n k(k+1) = {n(n+1)(n+2)\over 3}$ by
induction.

For the case $n = 1,$ $1\cdot 2 = {1(1+1)(1+2)\over 3} = 6/3 = 2.$

In the inductive case, assume that this statement is true for some $n
\geq 1,$ giving
$$\sum_{k=1}^n k(k+1) = {n(n+1)(n+2)\over 3}.$$
We will show that this statement is true for $n+1:$
$$\sum_{k=1}^{n+1} k(k+1) = {(n+1)(n+2)(n+3)\over 3}.$$
This is true only if
$$\sum_{k=1}^{n+1} k(k+1) - \sum_{k=1}^n k(k+1) = (n+1)(n+2) =
{(n+1)(n+2)(n+3)\over 3} - {n(n+1)(n+2)\over 3}.$$

$${(n+1)(n+2)(n+3)\over 3} - {n(n+1)(n+2)\over 3} =
{(n+3-n)(n+1)(n+2)\over 3} = (n+1)(n+2),$$
thus proving the statement for $n+1.$

Therefore, this identity is true for all $j\in\bb N.$
\endanswer

\problem{8.} If $n\in\bb N,$ then ${1\over 2!} + {2\over 3!} + {3\over
4!} + \cdots + {n\over (n+1)!} = 1 - {1\over (n+1)!}$

\answer
We will show this statement for all $n\in\bb N$ by induction.

In the base case $n = 1,$ ${1\over 2!} = 1/2 = 1 - {1\over 2!},$ so the
statement is true.

In the inductive case, assume that the statement is true for some $n\geq
1.$ We will show the statement for $n+1:$
$${1\over 2!} + {2\over 3!} + \cdots + {n+1\over (n+2)!} = 1 - {1\over
(n+2)!}.$$
Then,
$$1-{1\over (n+2)!} = 1-{n+2\over(n+2)!}+{n+1\over (n+2)!} = 1-{1\over
(n+1)!} + {n+1\over (n+2)!}.$$
By the inductive hypothesis,
$$1-{1\over (n+1)!} + {n+1\over (n+2)!} = {1\over 2!} + {2\over 3!} +
\cdots + {n\over (n+1)!} + {n+1\over (n+2)!},$$
proving our inductive step.

Therefore, for all $j\in\bb N,$ this identity is true.
\endanswer

\problem{20.} Prove that $(1+2+3+\cdots+n)^2 = 1^3 + 2^3 + 3^3 + \cdots
+ n^3$ for every $n\in\bb N.$

\answer
We will show this identity for all $n\in\bb N$ by induction.

In the base case, $1^2 = 1^3,$ so the statement is immediate.

In the inductive case, assume $(1+2+3+\cdots+k)^2 = 1^3 + 2^3 + 3^3 +
\cdots + k^3$ for some $k\in\bb N.$
We will show that $(1+2+3+\cdots+k+(k+1))^2 = 1^3 + 2^3 + 3^3 + \cdots +
(k+1)^3.$

$$(1+2+\cdots+k+(k+1))^2 = (1+2+\cdots+k)^2 + 2(1+2+\cdots+k)(k+1) +
(k+1)^2.$$
With the result $1+2+\cdots+k = {k(k+1)\over 2},$
we get this equal to
$$(1+2+\cdots+k)^2 + k(k+1)(k+1) + 1(k+1)^2,$$
and from the inductive hypothesis, this is equal to
$$1^3 + 2^3 + \cdots + k^3 + k(k+1)(k+1) + 1(k+1)^2 = 1^3 + 2^3 + \cdots
+ k^3 + (k+1)^3.$$

We have thus proven that for any $n\in\bb N,$ $(1+2+3+\cdots+n)^2 = 1^3
+ 2^3 + 3^3 + \cdots + n^3.$
\endanswer

\problem{26.} Concerning the Fibonacci sequence, prove that
$\sum_{k=1}^n F_k^2 = F_nF_{n+1}.$

\answer
We will show this identity, for all $n\in\bb Z$ s.t. $n\geq 1,$ by
induction.

For $n=1,$ $F_1^2 = 1 = F_1F_2.$

Assume for some $n\geq 1,$ $\sum_{k=1}^n F_k^2 = F_nF_{n+1}.$
We will show the statement for $n+1:$
$$\sum_{k=1}^{n+1} F_k^2 = F_{n+1}F_{n+2}.$$
We get the following from the definition of the Fibonacci numbers above
2:
$$F_{n+1}F_{n+2} = F_{n+1}(F_n + F_{n+1}) = F_{n+1}^2 + F_{n+1}F_n,$$
and from our inductive hypothesis,
$$F_{n+1}^2 + F_{n+1}F_n = F_{n+1}^2 + \sum_{k=1}^n F_k^2 =
\sum_{k=1}^{n+1} F_k^2,$$
completing our inductive step.

This shows that for all $j\in\bb Z,$ where $j\geq 1,$
$$\sum_{k=1}^j F_k^2 = F_jF_{j+1}.$$
\endanswer

\section{Hammack 11.1: 4, 14, 15}

\problem{4.}
Let $A = \{a,b,c,d\}.$ Suppose $R$ is the relation
$$\vbox{\halign{&\quad$#$\quad\cr
    R&=&\{(a,a),(b,b),(c,c),(d,d),(a,b),(b,a),(a,c),(c,a),\cr
    &&(a,d),(d,a),(b,c),(c,b),(b,d),(d,b),(c,d),(d,c)\}\cr
}}$$
Is R Reflexive? Symmetric? Transitive? If a property does not hold, say
why.

\answer
This is reflexive, symmetric, and transitive.
\endanswer

\problem{14.}
Suppose $R$ is symmetric and transitive relation on set $A,$ and there
is an element $a\in A$ for which $aRx$ for every $x\in A.$ Prove that
$R$ is reflexive.

\answer
For every $x\in A,$ $aRx$ is given and $xRa$ by symmetry. By
transitivity, $xRx$ for every element, so the relationship is reflexive.
\endanswer

\problem{15.} Prove or disprove: if a relation is symmetric and
transitive, then it is also reflexive.

\answer
The empty relation $\emptyset$ is vacuously symmetric and transitive but
on a nonempty set containing $x,$ the empty relation doesn't contain
$(x,x).$
\endanswer

\section{Hammack 11.2: 6, 8, 10, 12}

\problem{6.} Let $A = \{1,2,3,4,5,6\},$ and consider the following
equivalence relation on $A:$ $$R =
\{(1,1),(2,2),(3,3),(4,4),(5,5),(6,6),(2,3),(3,2),(4,5),(5,4),(4,6),
(6,4),(5,6),(6,5)\}.$$
List the equivalence classes of $R.$

\answer
The equivalence classes are $\{2,3\},$ $\{4,5,6\},$ and $\{1\}.$
\endanswer

\problem{8.} Define a relation $R$ on $\bb Z$ as $xRy$ if and only if
$x^2+y^2$ is even. Prove $R$ is an equivalence relation. Describe its
equivalence classes.

\answer
$R$ is reflexive, symmetric, and transitive, so it is an equivalence
relation.
The relation is reflexive because $x^2 + x^2 = 2(x^2),$ and $x^2\in\bb
Z,$ so the sum is even.
The relation is symmetric because $x^2 + y^2 = y^2 + x^2,$ so the left
side is even if and only if the right side is even.
And for some $j,k\in\bb Z,$ $xRy$ and $yRz$ implies $x^2+y^2 = 2j$ and
$y^2+z^2 = 2k,$ so $x^2 + y^2 + y^2 + z^2 - 2y^2 = x^2 + z^2 =
2(j+k-y^2).$
The number $j+k-y^2\in\bb Z,$ so $xRz,$ and the relation is transitive.

The equivalence classes are the even numbers and the odd numbers.
\endanswer

\problem{10.} Suppose $R$ and $S$ are two equivalence relations on a set
$A.$ Prove that $R\cap S$ is also an equivalence relation.

\answer
The equivalence relations $R$ and $S$ on $A$ are, by definition,
reflexive, symmetric, and transitive.
$R\cap S$ is therefore reflexive because $x\in A$ implies $(x,x)\in R$
and $(x,x)\in S,$ (by reflection), so $(x,x)\in R\cap S.$

Only if $xRy$ and $xSy,$ $x(R\cap S)y,$ and by symmetry, $yRx$ and
$ySx,$ so $y(R\cap S)x,$ giving symmetry of the new relation.

Similarly, if $x(R\cap S)y$ and $y(R\cap S)z,$ $xRy$ and $xRz,$ so by
transitivity, $xRz,$ and similarly, $xSz,$ so $x(R\cap S)z,$ making the
intersection of any equivalence relations also an equivalence relation.
\endanswer

\problem{12.} Prove or disprove: If $R$ and $S$ are two equivalence
relations on a set $A,$ then $R\cup S$ is also an equivalence relation
on $A.$

\answer
{\bf Disproof.}

Let $R$ be a relation with equivalence classes $\{1,2\}, \{3\}$ and $S$
be a relation with equivalence classes $\{1\}, \{2,3\}.$ $\{(1,2),
(2,3)\} \subseteq R\cup S,$ but $(1,3)\not\in R\cup S$ because
$1\mathbin{\not\hskip-3pt R} 3$ and $1\mathbin{\not\hskip-2pt S} 3.$
\endanswer

\bye